Evolución del consumo de vancomicina 500 mg, en pacientes hospitalizados en los servicios de medicina, cirugía, cuidados intensivos – intermedios del Hospital Víctor Lazarte Echegaray, periodo 2012-2014 - Llamoctanta Palma, Diana Elizabeth (2015)
Studies of drug use have become a useful tool to identify patterns, profiles and other features of use in clinical practice of medicine and especially of antimicrobials are tool whose misuse is leading to increased resistance antibacterial. In this paper we have made a study of the evolution of consumption of antimicrobial booking as vancomycin, in order to provide information about how it has evolved this antibiotic consumption in hospitals during the period 2012-2014 . An observational descriptive study was conducted retrospective. ATC / DDD methodology for calculating consumption 500mg vancomycin was used. services in medicine, surgery, ICU and NICU and the consumption value expressed in soles was calculated consumption trends over time and the correlation between variables were established using the linear regression analysis, it is accepted as a criterion for significance the value of p <0.05. and in ICU 6.34DDD / 100 bed-days he rose to 11.88DDD / 100: increased consumption of vancomycin (expressed in DDD / 100 bed-days) and ICU Medical, during the three years was increased consumption was found day-beds and medicine 4.33 DDD / 100 bed-days to 6.53 DDD / 100 bed-days in Surgery 1.84 DDD / 100 bed-days to 3.07 DDD / 100 bed-days and the service was a decrease in NICU 2.13 DDD / 100 bed-days to 1.57 DDD / 100 bed-days. The trend of total annual consumption grew in 2012 (3.67DDD / 100 bed-days) 2014 (5.76DDD / 100 bed-days) and the trend in consumer spending was directly proportional as it increased from 2012 to 2014, but It was not statistically significant (p = 0.12). Finally it is concluded that the consumption of vancomycin in hospitalized patients in the Hospital Victor Lazarte Echegaray has increased significantly over the three years of study